The Effect of Climate Change on Captured Fish Production in Batam - Jabnabillah, Faradiba; Reza, Widya (Jurnal Media Akuakultur Indonesia, 2024)
Batam is one of the cities in Indonesia which is located in a strategic area which is on international shipping lanes and has a sea area of 3,675 km2, so it has enormous potential in the field of marine fisheries resources. The catch of fishermen is strongly influenced by wind, temperature and rainfall. However, the main factor that is often a problem for fishermen at sea is global warming which is increasing which causes changing patterns of wind, temperature and rainfall to become erratic which makes it difficult for fishermen to catch fish. This study aims to describe the effect of temperature, wind speed and rainfall on capture fish production in the city of Batam. The research method used is quantitative using the time series regression test which was analyzed starting from January 2016 to December 2020 with the variables analyzed being temperature (X1), wind speed (X2), rainfall (X3) and capture fisheries production (Y). The results of the partial test show that the relationship between wind speed (X2) and rainfall (X3) to Y is negative, meaning that the higher the wind speed (X2) and rainfall (X3), the less catch fish production (Y) will be. While the partial test results show that temperature (X1), wind speed (X2) and rainfall (X3) together have a significant effect on capture fisheries production (Y) in the city of Batam.